2014
DOI: 10.4088/jcp.13m08725
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Clinical Effect of Low-Dose Buprenorphine for Treatment-Resistant Depression in Midlife and Older Adults

Abstract: Objective Describe the clinical effect and safety of low-dose buprenorphine, a kappa-opioid receptor antagonist, for treatment-resistant depression (TRD) in mid-life and older adults. Method Using an open-label protocol, buprenorphine was prescribed for 15 adults age 50 and older with TRD, diagnosed with the SCID for DSM-IV, between 6/2010-6/2011. The titrated dose of buprenorphine ranged from 0.2 mg-1.6 mg/day. We assessed clinical change in depression, anxiety, sleep, positive and negative affect, and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 44 publications
6
132
0
Order By: Relevance
“…Therefore, it is a suitable treatment choice for refractory depression, anxiety, self-injurious behaviors, and suicidal ideation (6,7,(14)(15)(16)(17). In the present report, we observed that 8 mg of buprenorphine had a rapid effect on the reduction and cessation of suicidal thoughts and depression.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, it is a suitable treatment choice for refractory depression, anxiety, self-injurious behaviors, and suicidal ideation (6,7,(14)(15)(16)(17). In the present report, we observed that 8 mg of buprenorphine had a rapid effect on the reduction and cessation of suicidal thoughts and depression.…”
Section: Discussionsupporting
confidence: 53%
“…Overall, buprenorphine reduces physiological and subjective responses to social stressors, including social rejection (14). In this regard, Karp et al demonstrated the effectiveness of lowdose buprenorphine for treatment-resistant depression in older adults (17). Norelli et al also successfully treated severe self-injurious behaviors with buprenorphine (16).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and pre-clinical studies have demonstrated the efficacy of buprenorphine and its novel analogues in the pharmacotherapy Review Danuta Szkutnik-Fiedler of depression [3,[71][72][73][74][75][76]. Ahmadi et al [73] suggest that a single high-dose of buprenorphine provides a safe, speedy and straightforward means of depression, especially in patients who are opioid dependent.…”
Section: Buprenorphine and Its New Analoguesmentioning
confidence: 99%
“…Almatroudi et al [75] also showed that co-administration of buprenorphine with naltrexone in CD-1 mice produced an antidepressant-like response in behaviours in both the forced swim test and novelty-induced hypophagia task what means that this combination represents a novel approach, to the treatment of depression. According to a study by Karp et al [71], buprenorphine provides rapid and sustained improvement for older adults with treatment-resistant depression. A low-dose of buprenorphine sharply decreased major depression severity during the first three weeks of treatment.…”
Section: Buprenorphine and Its New Analoguesmentioning
confidence: 99%
“…A more 'out of the box approach' is to take advantage of "creative" pharmacology. Buprenorphine is not only a mu partial agonist, but is a potent kappa antagonist having antidepressant activity (Karp et al, 2014). A recent open label clinical trial by Alkermes demonstrated that the nonselective KOR antagonist buprenorphine when combined with a mu opioid antagonist significantly reduced depressive symptoms in a population of individuals having treatment resistant depression (E. Ehrich, Kappa-2015 conference proceedings).…”
Section: Stress Of Addictionmentioning
confidence: 99%